Evaluation of uterine factors in patients with recurrent pregnancy loss by office hysteroscopy: a prospective and retrospective study - Sirsam, Shyamkumar S.; Mirge, Neha; Rathi, Arun; Karale, Vivek; Ajmera, Ankush (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy loss or miscarriage, occurs before 20 weeks, often due to chromosomal issues. Recurrent pregnancy loss (RPL), defined as two or more consecutive losses, has various causes. Office hysteroscopy is the gold standard for diagnosing uterine anomalies, improving accuracy and patient comfort in RPL management. The study aims to evaluate uterine factors in patients of recurrent pregnancy loss by office hysteroscopy. Methods: This prospective study was conducted over 18 months (June 2023 to December 2024) Department of Obstetrics and Gynaecology at Department of Obstetrics and Gynaecology at Government Medical College, Akola, Maharashtra. All patients with a history of recurrent pregnancy loss attending the outpatient department (OPD) during the study period were included using universal sampling method. Results: Among 132 women with recurrent pregnancy loss (RPL), the mean age was 27.75±4.6 years and mean duration of marriage was 5±2.04 years. Overweight and obesity were common (78%) and acquired uterine anomalies (54.16%) slightly exceeded congenital ones (45.83%). Office hysteroscopy detected more uterine abnormalities than transvaginal sonography, confirming its superior diagnostic yield with minimal procedural complications. Conclusions: Office hysteroscopy demonstrated high diagnostic accuracy and safety in evaluating uterine abnormalities among women with recurrent pregnancy loss. It effectively identified both congenital and acquired intrauterine pathologies, outperforming transvaginal sonography and proved valuable as both a diagnostic and therapeutic tool for improving reproductive outcomes in affected women.